IoT-Based Duck Egg Incubator with Automatic Turning Feature to Increase Productivity - Dian Yola Lestari; Asrizal Asrizal; Mona Berlian Sari (RESSTECH, 2025)
Duck farming has great potential in Indonesia but still faces the challenge of low hatching success rates due to inefficient manual incubation methods. The stability of temperature and humidity, as well as the accuracy of egg turning schedules, are critical factors in supporting successful incubation. To address these issues, this research aims to design and develop an IoT-based duck egg incubator with an automatic turning feature to improve hatching productivity. The system is built using an ESP32 microcontroller, a DHT22 sensor for detecting temperature and humidity, a DS3231 RTC module for automatic egg turning scheduling, and the Blynk application as a platform for remote monitoring and control via a smartphone. The research method used is engineering-based, which includes literature study, hardware and software design, prototype development, system performance testing, and result analysis. The incubator is designed in a box shape measuring 60×40×40 cm with a capacity of approximately 50 eggs. The main components consist of three incandescent lamps as the heat source, a cooling fan, an automatic egg rack driven by an AC motor, and a monitoring system based on an LCD and the Blynk application. Test results show that the device is capable of maintaining an average temperature of 37.9°C and humidity of 62.2%, with standard deviations of ±0.63°C and ±1.90%, respectively — all within the ideal range for duck egg incubation. The DHT22 sensor demonstrated a high level of accuracy, with a precision rate of 99.81% for temperature and 99.15% for humidity when compared to standard measuring instruments. The accuracy of the temperature measurement was 99.84%, and for humidity, it was 99.18%, indicating that the DHT22 sensor performs excellently in terms of precision and stability. The automatic turning feature operates according to the pre-set schedule, specifically at 00:00, 06:00, 12:00, and 18:00 WIB, with each turning lasting two minutes. Temperature and humidity data monitoring through the LCD and Blynk application produced consistent and synchronized results. Initial testing with 50 duck eggs showed a hatching success rate of 91%. Based on these results, it can be concluded that the device has good design specifications and performance, is stable in maintaining incubation conditions, and is efficient and practical to use. This system is feasible to be applied as a technological solution in modern duck farming.